2021
DOI: 10.1186/s12968-021-00762-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac biomarkers in chronic kidney disease are independently associated with myocardial edema and diffuse fibrosis by cardiovascular magnetic resonance

Abstract: Background High sensitivity cardiac troponin T (hs-cTnT) and NT-pro-brain natriuretic peptide (NT-pro BNP) are often elevated in chronic kidney disease (CKD) and associated with both cardiovascular remodeling and outcome. Relationship between these biomarkers and quantitative imaging measures of myocardial fibrosis and edema by T1 and T2 mapping remains unknown. Methods Consecutive patients with established CKD and estimated glomerular filtration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…[ 24 ] Moreover, native T 1 values were independently associated with clinical variables, such as physical function and cardiac biomarkers. [ 20 , 25 , 26 ]…”
Section: T 1 and T 2 Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 24 ] Moreover, native T 1 values were independently associated with clinical variables, such as physical function and cardiac biomarkers. [ 20 , 25 , 26 ]…”
Section: T 1 and T 2 Mappingmentioning
confidence: 99%
“…A recent study in CKD patients referred with a clinical indication for contrast CMR imaging found that LGE prevalence was similar to that described previously. [ 26 ] Although in diffuse diseases the method of a conservative mid-septal ROI is suggested for assessing native T 1 , areas of visually increased signal may be found, suggesting local fibrosis. [ 32 , 33 ] A study sought to investigate the ability of native T 1 to identify replacement fibrosis in aortic stenosis as a model for use in ESRD, but a defined threshold for the identification of scarred areas could not be identified.…”
Section: T 1 and T 2 Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology behind myocardial derangements in chronic kidney disease is complex; however, especially in the context of longitudinal systolic and diastolic abnormalities, the contribution of diffuse tissue processes including interstitial fluid retention and fibrosis should be emphasized [29].…”
Section: Discussionmentioning
confidence: 99%
“…9). Hypertension and reduced renal clearance of waste products have both been proposed to contribute to the increased incidence of cardiac fibrosis seen even in early experimental and human CKD [31][32][33] . Returning to our model of transgenic Ihh depletion confined to Pax8 expressing epithelia with maintained cardiac Ihh expression (due to negligible cardiac Pax8 expression left unaltered by Tamoxifen, Online Data and Extended Data Fig.…”
Section: Renal Injury Induces Transcriptional Changes In Remote Organsmentioning
confidence: 99%